Education in agricultural sector: Evidence from a systematic literature review and validation in Spain for policy recommendations - Rodrigo Menor de Gaspar López (Journal of Science and Inclusive Development, 2026)
The broadly acknowledged positive impact of education on the economy as a whole has received significant attention; however, the agricultural sector itself has been largely overlooked in economic development. A systematic literature review was conducted using the Scopus database to ascertain the academic consensus on the impact of education in the agricultural sector. Subsequent analysis compared the findings with the reality of Spain, and the results were replicated. It is posited that recommendations for educational policies, in both their general and agricultural applications, are applicable to the agricultural sector irrespective of a nation's level of development. It is imperative to enhance fundamental education and devise targeted policies to foster learning in rural contexts. This approach leverages the potential of effective training to encourage self-directed learning and the integration of Information and Communication Technologies (ICTs). Policies prioritize the dissemination of knowledge concerning adaptation, technification, and management. Moreover, these policies should incentivize interest groups, such as young people and women, and facilitate credit for innovation.